2018
DOI: 10.1038/s41433-018-0019-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the timing of the cessation of contact lens use on the results of biometry

Abstract: There is a significant variation in UK practice regarding advice on the timing of cessation of contact lens wear prior to having biometry performed. Our study suggests that it is likely that soft contact lens wearers are currently being advised to remove their contact lenses for an unnecessarily long period of time prior to having biometry performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…Furthermore, contact lens wearers were only instructed to remove their contact lenses 24 hours prior to scanning to minimize inconvenience and maximize participation for those who routinely wear contacts to achieve functional vision. Moreover, some studies demonstrate that soft contact lens users, which were the majority in our cohort, do not exhibit significant alterations in corneal shape [36]. In addition, a histopathological study showed that the duration of contact lens wear did not affect central epithelial pattern types in patients with keratoconus [37].…”
Section: Plos Onementioning
confidence: 58%
“…Furthermore, contact lens wearers were only instructed to remove their contact lenses 24 hours prior to scanning to minimize inconvenience and maximize participation for those who routinely wear contacts to achieve functional vision. Moreover, some studies demonstrate that soft contact lens users, which were the majority in our cohort, do not exhibit significant alterations in corneal shape [36]. In addition, a histopathological study showed that the duration of contact lens wear did not affect central epithelial pattern types in patients with keratoconus [37].…”
Section: Plos Onementioning
confidence: 58%
“…We did not have a healthy control group and we also included some scans of acceptable but not ideal quality, which we feel is a realistic representation of a clinical setting where patients with keratoconus often have scans of suboptimal quality. Moreover, contact lens wearers were only required to remove their contact lenses for 48 hours prior, however, a study has shown that soft contact lens, does not induce significant alteration in corneal shape or subsequent biometric measurements [ 36 ]. While this study has a modest number of participants, future studies with larger numbers across a variety of pathologies can help us to better understand the application of these devices in patients with keratoconus.…”
Section: Discussionmentioning
confidence: 99%
“…Subjects were excluded where there was a history of ocular diseases (other than KC), history of trauma or ocular surgery, and intraocular pressure (IOP) above 21 mmHg as measured by Ocular Response Analyser (Reichert Technologies, Depew, NY, USA). If the subjects wore contact lenses, they were required to stop wearing them for a period of time before topography measurement [19]; soft contact lens wearers were asked to remove lenses two weeks prior to measurements and rigid, gas-permeable (RGP), four weeks prior.…”
Section: Subject Data Collection and Processingmentioning
confidence: 99%